(untitled) (Revista Electrónica Calidad en la Educación Superior, 2020)
Although this paper stipules the theoretical position, it is very important to analyze the conflicts from a comparative perspective. “That implies recognizing and knowing the processes and the parties involved that give meaning to similar academic structures. However, the parties involved and their orientations, as well as the values and practices that explain the future of the university, are remarkably different, although curiously some result indicators are similar for the region as a whole” (Krotsch, 2006). However, we could ask ourselves if there is a common socioeconomic and cultural pattern for the region that determines a university model? The tentative answer would be yes, keeping their distances, especially at the practical procedural level of university policies. Taking into consideration, the regional features and the six analytical axes and six groups of university policies that are mentioned, in addition to the university policies that are applied. The objetive of the article is to analyze in a comparative way the results of a group of six university policies at the undergraduate and postgraduate levels at Latin American universities in countries of similar development such as Brazil, Chile, Argentina and Mexico, mainly and referentially compare them some important. As well as presenting the main desirable and possible scenarios as trends of those policies towards 2030 based on prospective planning.